Sense of place in everyday spaces:: lessons for urban design - Mehta, Vikas (ARCC Conference Repository, 2018)
Many philosophers and thinkers have lamented the loss of place in terms of the loss of contact of the body with the environment in post-industrialized societies. With the diminishing cache of places it becomes even more important to study spaces in the city that posses this character and genius loci. This paper investigates the qualities of a seemingly ordinary everyday space that imbue it with character and elevate it to become a place. The paper explores the significance of this space in everyday life and how it is transformed from an ordinary space of consumption to a meaningful place for meeting, interaction and human-human contacts, and a place for haptic experiences and bodyobject contacts in the community. An extensive study of a neighborhood commercial street in Cambridge, Massachusetts revealed a handful of spaces that were extensively used for social interactions. Observations and interviews suggested that one of these spaces supported the majority of social interactions and was a concrete human space with a unique sense of place. The patterns of interactions at this location were documented and analyzed using sketches, drawings, notes, interviews, photographs and videos and by actively participating in the phenomena of this space. Observations show that this location on the street has a distinct hereness, a sense of being in it and enclosure, a sense of ease and safety that is at the core of the experience of place. By analyzing the various phenomena of this place this study suggests essential qualities for the design of public spaces to become places that will retain a sense of nearness, a connection between people and places, and will strengthen our sense of tactile reality.